Hubungan Minat Kejuruan dengan Kesiapan Memasuki Dunia Kerja Siswa Teknik Kendaraan Ringan Otomotif (Tkro) Smk Negeri 2 Sungai Penuh - M. Hifzon Fadhlika; Hasan Maksum; Irma Yulia Basri; Rifdarmon Rifdarmon (Jurnal Kendali Teknik dan Sains, 2026)
This research focuses on the vocational interest and readiness to enter the workforce of students in the Light Automotive Engineering (TKRO) program at SMK Negeri 2 Sungai Penuh. The purpose of this study is to determine the relationship between students' vocational interest and their readiness to enter the workforce. This type of research is a descriptive study with a correlational approach. The study involved 64 students enrolled in Light Automotive Engineering (TKRO). The sample size taken for this research was 39 students, selected through stratified random sampling using the Taro Yamane formula. Questionnaires that have been declared valid and reliable were utilized to collect data regarding the students' vocational interest and their readiness to enter the workforce. The data analysis was conducted using the Product Moment correlation formula. The results of the data analysis indicate a positive and significant relationship between vocational interest and the readiness to enter the workforce among Light Automotive Engineering (TKRO) students at SMK Negeri 2 Sungai Penuh, with a correlation coefficient of 0.442 (greater than 0.316) and a significance coefficient of 2.9982 (greater than 2.02269) at a 5% significance level.